2021
DOI: 10.1128/msystems.00934-21
|View full text |Cite
|
Sign up to set email alerts
|

Lineage-Specific Growth Curves Document Large Differences in Response of Individual Groups of Marine Bacteria to the Top-Down and Bottom-Up Controls

Abstract: Growth is one of the main manifestations of life. It is assumed generally that bacterial growth is constrained mostly by nutrient availability (bottom-up control) and grazing (top-down control).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 69 publications
1
19
0
Order By: Relevance
“…Differences in phosphate and phosphonate transporter protein abundance have been observed between the oligotrophic Sargasso Sea and nutrient-rich upwelling areas (65, 66), but not on these finer temporal and spatial scales. A more recent study using incubations of microbial communities demonstrated that SAR11 increased growth rates with the addition of phosphate but not the elimination of grazers (29). Phosphate starvation or possibly increases in phosphonate also may lead to large changes in SAR11 metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in phosphate and phosphonate transporter protein abundance have been observed between the oligotrophic Sargasso Sea and nutrient-rich upwelling areas (65, 66), but not on these finer temporal and spatial scales. A more recent study using incubations of microbial communities demonstrated that SAR11 increased growth rates with the addition of phosphate but not the elimination of grazers (29). Phosphate starvation or possibly increases in phosphonate also may lead to large changes in SAR11 metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous estimates by our group using 16S rRNA gene:rRNA ratios in the coastal Mid-Atlantic suggest that about half of the SAR11 taxa had lower growth rates than average, whereas the other half had average or above average growth rates, which varied by season (26). Differential use of glucose and phosphate was also observed within the SAR11 clade, likely contributing to differences in ocean productivity (27, 28) and perhaps also to growth rate (29). In addition, data from a technique combining microautoradiography and fluorescence in situ hybridization (MAR-FISH) suggest that SAR11 bacteria are in fact growing as fast, if not faster than other bacteria in surface waters of the North Atlantic (30, 31).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, molecular methods were used for the first time to determine bacterial diversity in open areas of the central and southern Adriatic Sea, and the use of Neural Gas showed a heterogeneous response to different environmental factors (Šantić et al, 2021). Moreover, in Kaštela Bay, qualitative annotation by amplicon reads with normalization by the standard internal method was applied for the first time to determine the growth curves of different phylotypes of bacteria and AAPs using the 16S rRNA and pufM genes (Fecskeová et al, 2021) and compared them with counts by microscopy and catalyzed reporter deposition -fluorescence in situ hybridization (CARD-FISH).…”
Section: Influence Of Environmental Factors On Aerobic Anoxygenic Pho...mentioning
confidence: 99%
“…Studies have been carried out on the proportion of individual picoplankton groups under specific environmental conditions 11 13 , but data on the year-round qualitative and quantitative response of picoplankton in general is limited. Therefore, this study provides the first comprehensive insight into the seasonal and spatial dynamics of the picoplankton community in the Adriatic Sea in terms of abundance, the dynamics of major bacterial groups, and archaeal and bacterial diversity.…”
Section: Introductionmentioning
confidence: 99%